PENGARUH KOMPETENSI, INDEPENDENSI, AKUNTABILITAS DAN MOTIVASI TERHADAP KUALITAS AUDIT (STUDI EMPIRIS AUDITOR EKSTERNAL DI KANTOR AKUNTAN PUBLIK SEMARANG) - Nuriyana Rizki, 14.05.52.0126; Kartika, Andi (Students' Journal of Accounting and Banking, 2019)
Factors that influence audit quality are cometency, independence, accountability and motivation. This study aims to examine the effect of competency, ndependence, accountability and motivation on audit quality. The population in this study were all auditors who worked at the Public Accounting Firm in Semarang. Sampling was done using the convenience sampling method and obtained a sample of 56 respondents. The primary data collection method is done through survey methods using a questionnaire. The data obtained using multiple linear model. The results of this study indicate that competence, independence, accountability and motivation affect audit quality.